Fate of carbohydrates and lignin in north-east Siberian permafrost soils. (January 2018) - Dao, Thao Thi; Gentsch, Norman; Mikutta, Robert; Sauheitl, Leopold; Shibistova, Olga; Wild, Birgit; Schnecker, Jörg; Bárta, Jiří; Čapek, Petr; Gittel, Antje; Lashchinskiy, Nikolay; Urich, Tim; et al.
Abstract: Permafrost soils preserve huge amounts of organic carbon (OC) prone to decomposition under changing climatic conditions. However, knowledge on the composition of soil organic matter (OM) and its transformation and vulnerability to decomposition in these soils is scarce. We determined neutral sugars and lignin-derived phenols, released by trifluoroacetic acid (TFA) and CuO oxidation, respectively, within plants and soil density fractions from the active layer and the upper permafrost layer at three different tundra types (shrubby grass, shrubby tussock, shrubby lichen) in the Northeast Siberian Arctic. The heavy fraction (HF; >1.6 g mL −1 ) was characterized by a larger enrichment of microbial sugars (hexoses vs. pentoses) and more pronounced lignin degradation (acids vs. aldehydes) as compared to the light fraction (LF; <1.6 g mL −1 ), showing the transformation from plant residue-dominated particulate OM to a largely microbial imprint in mineral-associated OM. In contrast to temperate and tropical soils, total neutral sugar contents and galactose plus mannose to arabinose plus xylose ratios (GM/AX) decreased in the HF with soil depth, which may indicate a process of effective recycling of microbial biomass rather than utilizing old plant materials. At the same time, lignin-derived phenols increased and the degree of oxidative decomposition of lignin decreased with soil depth, suggesting a selective preservation of lignin presumably due to anaerobiosis. As large parts of the plant-derived pentoses are incorporated in lignocelluloses and thereby protected against rapid decomposition, this might also explain the relative enrichment of pentoses with soil depth. Hence, our results show a relatively large contribution of plant-derived OM, particularly in the buried topsoil and subsoil, which is stabilized by the current soil environmental conditions but may become available to decomposers if permafrost degradation promotes soil drainage and improves the soil oxygen supply. Highlights: The patterns of carbohydrate and lignin decomposition in the studied permafrost soils deviate from those in temperate soils. Lignin and lignocellulose are selectively preserved. Microbial biomass, i.e., microbially-derived sugars appear to be effectively recycled.